Difference in bypass for inpatient care and its determinants between rural and urban residents in China - Shan Lu; Yunxiao Li; Hongxia Gao; Yan Zhang (BMC, 2022)
Abstract Background Bypass for inpatient care is an event of excessive demand. Though primary care facilities provide inpatient care in China, local residents may choose more distant higher-level hospital for inpatient care services. Given the differences in accessibility of hospitals and socioeconomic development between urban and rural areas, this study aims to estimate the rate of bypass for inpatient care and explore the factors predictive of bypass among rural and urban residents in China. Methods The rates of bypass for inpatient care were estimated using data from 1352 hospitalized patients, obtained from the 2018 Sixth National Health Service Survey of Hubei, China. Bypass for inpatient care was identified if the patient was hospitalized in a hospital for a certain disease that should be treated at primary care facilities in accordance with government requirement. Anderson's Behavioral Model of Health Services Use was used as a theoretical framework for determining the factors of bypass. Logistic regression was used to identify the relationship between bypass for inpatient care and predisposing, enabling, and need characteristics for urban and rural residents. Results The rate of bypass for inpatient care was 73.8%. This rate for inpatient care (91.3%) in cities is higher than that in rural areas (56.2%). Age were associated with bypass for both rural (OR, 0.982; 95% CI, 0.969-0.995) and urban (OR, 0.947; 95% CI, 0.919-0.976) patients. The patients whose closest healthcare facility was hospitals were more likely to have bypass behavior in rural (OR, 26.091; 95% CI, 7.867-86.537) and urban (OR, 8.323; 95% CI, 2.936-23.591) areas than those living closest to township/community health centers. Signing a family doctor was not helpful for retaining patients at primary care facility. Among rural patients, those with circulatory (OR, 2.378; 95% CI, 1.328-4.258), digestive (OR, 2.317; 95% CI, 1.280-4.192), or skin and bone (OR, 1.758; 95% CI, 1.088-2.840) system diseases were more likely to show bypass behavior than those with respiratory diseases. Conclusions Bypass for inpatient care is sizable, and urban residents have a higher bypass rate for inpatient care than rural residents in China. More actionable measures in strengthening and leading patients to primary care are needed. Gradual establishment of a referral system is recommended. Inpatient care for circulatory, digestive, or skin and bone system diseases may be prioritized to be improved at primary care facilities in rural China.